2011
DOI: 10.1111/j.1442-200x.2010.03142.x
|View full text |Cite
|
Sign up to set email alerts
|

Remission of high‐grade B‐cell lymphoma in a pediatric patient following Helicobacter pylori eradication

Abstract: A rational approach for assessing the hypothalamo-pituitary-adrenal axis. Lancet 1988; 1(8596): 1208-10. 8 Tuchelt H, Dekker K, Bähr V, Oelkers W. Dose-response relationship between plasma ACTH and serum cortisol in the insulin-hypoglycaemia test in 25 healthy subjects and 109 patients with pituitary disease. Clin. Endocrinol. (Oxf.) 2000; 53: 301-7. 9 Schober E, Frisch H. Growth retardation and reduced growth hormone secretion in a boy with achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…34,37 Considering these facts, histological improvement may be expected after H. pylori is eradicated in the infected children with chronic gastritis. Comments There is only one review 8 and three case reports [38][39][40] about H. pylori eradication therapies for MALT lymphoma in children. In a 14-year-old American girl with H. pylori-positive gastritis and low-grade MALT lymphoma, the lymphoproliferative lesion was improved with the eradication therapy and no recurrence of the lesion was detected at 7 year follow up.…”
Section: [Clinical Question 3]mentioning
confidence: 99%
See 2 more Smart Citations
“…34,37 Considering these facts, histological improvement may be expected after H. pylori is eradicated in the infected children with chronic gastritis. Comments There is only one review 8 and three case reports [38][39][40] about H. pylori eradication therapies for MALT lymphoma in children. In a 14-year-old American girl with H. pylori-positive gastritis and low-grade MALT lymphoma, the lymphoproliferative lesion was improved with the eradication therapy and no recurrence of the lesion was detected at 7 year follow up.…”
Section: [Clinical Question 3]mentioning
confidence: 99%
“…39 In an 8-year-old Saudi Arabian boy with IDA and H. pylori-positive gastritis, high-grade B cell lymphoma was detected 3 months after completion of eradication therapy but the lymphoma lesion completely disappeared with continuing eradication therapy. 40 We recommend consideration of eradication therapy in children with gastric MALT lymphoma, when H. pylori infection is confirmed. Comments There are no systematic reviews or randomized controlled trials with regard to this clinical question.…”
Section: [Clinical Question 3]mentioning
confidence: 99%
See 1 more Smart Citation
“…If left untreated, it can cause chronic gastritis, peptic ulcer, gastric adenocarcinomas [7], and mucosa-associated lymphoid tissue (MALT) lymphomas [8]. Fortunately, H. pylori associated gastric cancer has not been reported in pediatric age group, but MALT lymphomas have been described in a few H. pylori infected children [911]. In an adult study, early eradication of H. pylori has been associated with a sixfold reduction in the recurrence of peptic ulcers as well as a twofold to threefold reduction in the risk of gastric carcinoma [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, a few cases of regression of these lymphomas after the cure of H. pylori infection have been described 80 . Thus, recent studies have shown that H. pylori eradication results in durable histological complete remission in approximately 50% of patients with large B‐cell lymphomas of the stomach with concomitant MALT areas 81–90 . As an example, Chen et al., 89 reported in a prospective study the disappearance of primary gastric large B‐cell lymphoma at gastroscopy examination in 14 of 22 patients (64%) after H. pylori eradication therapy.…”
Section: H Pylori Eradication Has No Role In the Treatment Of High‐gmentioning
confidence: 99%